Health Sector Reforms and Changes in Prevalence of Untreated Morbidity, Choice of Healthcare Providers among the Poor and Rural Population in India - Soumitra Ghosh (Kerman University of Medical Sciences, 2014)
Background India's health sector witnessed some major policy changes in 1990s that aimed at making health services more accessible to the population. Methods In this paper, I tried to present some preliminary results of the significant changes that occurred between 1995/6 and 2004, especially in relation to the question of access to healthcare for the poor and rural population using data from 52nd (1995-6) and 60th round (2004) of National Sample Survey Organization on 'morbidity and healthcare'. Results The analysis suggests that overall utilization of healthcare services have declined and the odds of not seeking care due to financial inability has further increased among the poor and rural population during the period of reforms. Results of the multivariate logit regression model indicate that the non-poor, middle and above educated people were having greater likelihood of using services from private health care provider. Conclusion Interestingly, poor and rural residents were more likely to have used healthcare from public facilities in 2004 than in 1995-6, suggesting that the shift from private to public sector is encouraging, provided they receive good quality health care services at public facilities and do not face catastrophic health expenditures.